Anti-inflammatory Effect of Astragalin and Chlorogenic Acid on Escherichia coli-Induced Inflammation of Sheep Endometrial Epithelium Cells - Hu, Xuequan; Wang, Meng; Pan, Yangyang; Xie, Yingying; Han, Jinhui; Zhang, Xingyun; Niayale, Robert; He, Honghong; Li, Qin; Zhao, Tian; Cui, Yan; Yu, Sijiu (Frontiers in Veterinary Science, 2020)
Endometritis is one of the main diseases which harm the sheep husbandry. Astragalin and chlorogenic acid (CGA) are common active ingredients of traditional Chinese medicine (TCM) with immunoprotective, antioxidant and anti-inflammatory properties. In the present study, sheep endometrial epithelium cells (SEECs) was successfully purified and identified, and the in vitro model of endometritis induced by Escherichia coli (E. coli) was successfully established. To explore the effect of Astragalin and CGA on the inflammation induced by E. coli and its potential mechanism, 6 groups were set up, including group C (SEECs were incubated with DMEM/F12 for 6 hr.), group M (SEECs were incubated with E. coli for 3 hr.), group Astragalin (SEECs were pre-treated with Astragalin for 3 hr. ahead of E. coli), group CGA (SEECs were pre-treated with CGA for 3 hr. ahead of E. coli), group BAY (SEECs were pre-treated with BAY for 3 hr. ahead of E. coli) and group STR (SEECs were pre-treated with STR (Streptomycin) for 3 hr. ahead of E. coli). After that, the total RNA and protein of each group were detected by qPCR, western blot and ELISA methods, respectively. The results showed that E. coli could obviously induce inflammation of SEECs in vitro, while Astragalin and CGA could alleviate the inflammatory response induced by E. coli via inhibiting the activation of TLR4/NF-κB signaling pathway, which provided a theoretical and experimental foundation for preventing sheep endometritis clinically.